Absence of Wharton's jelly: case report - Oliveira, Cristiano Claudino [UNESP] (2014)
There are few reports in the literature of the absence of Wharton's Jelly. Here we report the seventh case in a primigravida, 22 years old, admitted after vaginal delivery of stillborn. The umbilical cord have a long segment with disruption of cord structures and the three blood vessels were completely separated from each other, with a minimum amount of Wharton's jelly remaining around each vessel. The absence of Wharton' jelly is associated with fetal distress, intrauterine growth restriction, and fetal death. Quantitative/qualitative studies of Wharton's jelly represent an open field of research for possible correlations with obstetric conditions and fetal deaths.